The study of turn-taking In jane eyre movie 2011 - Abdullah, Id Haruddin Hanif; , Dra. Malikatul Laila, M.Hum (2016)
Turn-taking is important aspect of conversation. It can be said that it is the system to organize of the flow of conversation. To do a conversation, one must understand the techniques in taking a turn in conversation so the conversation goes smootly. This research analyzes about turn-taking used in the conversation in Jane Eyre Movie 2011 based on Sack (1974) theory of turn-taking. The aims of this research are (1) identifying the kind of turn-taking techniques the speaker used in Jane Eyre Movie 2011 and (2) examining the intention of each type of turn-taking used by the speaker in the movie. This research is analyzed using descriptive qualitative method since this research analyzes the data in words form. In analyzing data, the writer uses Sack's theory of turn-taking to answer the first problem and theory of context in discourse to answer the second problem. The writer took 14 data to be analyzed in this research. Based on Sack's theory, there are three turn-taking techniques, namely: Current speaker selects next technique, self-selection technique and current speaker continues technique. Based on data analysis, it is found that the most used technique is current speaker selects next technique which is used in 12 of 14 data, then followed by self-selection technique which is used in 10 of 14 data and the last current speaker continues technique which is used in 6 of 14 data. The speaker's intention of using current speaker selects next technique are to get a responses or demanding responses from the hearer. While the intention of using self-selection technique, the speaker has the intention to support or oppose the argument of the previous speaker and to give explanation of what is said by previous speaker. The intention of using current speaker continues technique is to convince the hearer. Another intention is to take some times to thinks of what next the speaker want to say.